The Impact of Health Belief Model-Based Education on Self-Care Behaviors of Hypertensive Patients - Parisa Kasmaei; Pegah Yousefi; Rabiollah Farmanbar; Saeed Omidi; Mahmood Karimy; Sedighe Bab Eghbal; Maryam Shakiba; Morvarid Molaee (Caspian Journal of Health Research)
Background: Hypertension is a prevalent health problem worldwide, affecting numerous individuals aged 35 and above. This study aimed to assess the influence of a health belief model (HBM)-based educational intervention on the self-care behaviors of hypertensive patients attending rural health centers in Rasht County. Methods: In this quasi-experimental study, 96 hypertensive patients were selected through a multi-stage method and randomly divided into experimental and control groups (48 samples per group). The data collection tool consisted of a valid questionnaire comprising four parts: demographic variables, knowledge, health belief model constructs, and self-care behaviors. The educational program, which involved five 45-minute sessions per group (four 12-sample groups) based on HBM, collected data twice before and three months after the educational intervention. Results: Before the educational intervention, mean scores for knowledge and health belief model constructs, self-care, and blood pressure were equal and showed no statistically significant difference between the intervention and control groups (p>0.05). However, after three months of the educational intervention, the mean scores of knowledge, self-care, and all HBM constructs, except for perceived barriers, increased significantly in the experimental group (p<0.05). Moreover, the patient's mean blood pressure scores significantly decreased in the experimental group. Conclusion: The substantial reduction in patients' blood pressure levels indicated the success of the health belief model-based intervention in enhancing self-care and blood pressure control in the target population. Therefore, an educational approach is recommended as an effective, cost-efficient, and safe solution in blood pressure control programs.